The Effect of Green Tax and Green Accounting on Firm Value Moderated by the Environmental Disclosure Index - Yanisa Zahra Nurul Fitria; Renita Rahmawati; Risdayanti Imelda Nurhasanah; Rafi Aldian (Fakultas Ekonomi Universitas Garut, 2025)
The global environmental crisis necessitates the integration of sustainability dimensions into corporate financial and accounting systems. This study aims to examine the effect of green tax and green accounting on firm value, with the environmental disclosure index (EDI) acting as a moderating variable. The study focuses on the consumer non-cyclicals sector listed on the Indonesia Stock Exchange for the period 2022–2024, using a quantitative associative approach with panel data. The estimation model employs the Estimated Generalized Least Squares (EGLS) method to address heteroskedasticity and autocorrelation issues. Results reveal that green accounting significantly and positively affects firm value, while green tax is not significant directly but becomes positively significant when moderated by EDI. Conversely, the interaction between green accounting and EDI shows a significant negative effect, indicating potential greenwashing or inconsistencies between disclosure and operational practices. These findings underscore the strategic importance of credible environmental disclosure in enhancing corporate legitimacy and market perception of sustainability strategies. This study offers updated empirical insights for strengthening environmental fiscal policy and corporate governance in emerging economies.